Artificial Intelligence Applied to Medical Imaging and Computational Biology - Rundo, Leonardo; Militello, Carmelo; Tangherloni, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Medical imaging and computational biology continuously pose new fundamental medical and biological questions that often give rise to novel challenges in Artificial Intelligence. These research fields present an increasing need for the application of cutting-edge computational approaches that generally involve machine learning or computational intelligence techniques, which can effectively perform bioimage and biosignal processing in different clinical areas.